2016
DOI: 10.19154/njwls.v6i2.4969
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Incivility in a Swedish Context

Abstract: The present study investigated workplace incivility in a Swedish context. The first aim was to assess how common the phenomenon is and the second was to study which groups (gender, age, ethnicity, and power position)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…This validates the conclusions drawn in previous studies, where relationships between experienced incivility and well-being were found (e.g. [ 24 26 ]). This demonstrates that incivility uniquely can contribute to the prediction of lower well-being when more severe mistreatment has been partialled out.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This validates the conclusions drawn in previous studies, where relationships between experienced incivility and well-being were found (e.g. [ 24 26 ]). This demonstrates that incivility uniquely can contribute to the prediction of lower well-being when more severe mistreatment has been partialled out.…”
Section: Discussionsupporting
confidence: 92%
“…Experienced workplace incivility has been related to lower levels of health and well-being in several studies [ 24 26 ]. There is therefore substantial support for the notion that workplace incivility has negative health effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most WI studies have been conducted in the Western context, especially in the USA and European countries (Sherrod & Lewallen, 2021; Smith et al, 2018; Torkelson et al, 2016). In contrast, the Asian context, which suggests the high-intensity increase of uncivil behavior in the workplace, has little academic attention (Alias et al, 2020; Arshad & Ismail, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Workplace incivility, defined as “low intensity deviant behavior with ambiguous intent to harm the target, in violation of workplace norms for mutual respect” (Andersson & Pearson, 1999, p. 457), is an insidious problem in workplaces around the world (Cortina, Magley, Williams, & Langhout, 2001; Kunkel, Carnevale, & Henderson, 2015; Schilpzand, De Pater, & Erez, 2016; Torkelson, Holm, & Bäckström, 2016; Yeung & Griffin, 2008). Porath and Pearson (2013) estimated that 98% of American workers have experienced some form of uncivil behavior, with up to 50% experiencing it on a weekly basis.…”
mentioning
confidence: 99%